EXTH-37. TARGETING EPIGENETIC VULNERABILITIES IDENTIFIED FROM A CRISPR SCREEN IN H3.3K27M DIPG. (9th November 2020) - Panditharatna, Eshini; Dharia, Neekesh; Li, Deyao; Beck, Alexander; Shaw, McKenzie; Jiang, Li; Trissal, Maria; Liu, Ilon; Lareau, Caleb; Anastas, Jamie; Quezada, Michael; Hack, Olivia; et al.
Abstract: Children diagnosed with diffuse intrinsic pontine glioma (DIPG), a type of high grade glioma in the brainstem, currently have a dismal 5-year overall survival of only 2%. The majority of DIPG patients harbor a K27M mutation in histone 3.3 encoding genes (H3.3K27M). To understand if the aberrant epigenetic landscape induced by H3.3K27M provides an opportunity for novel targeted therapies, we conducted the first CRISPR/Cas9 screen using a focused library of 1, 350 epigenetic regulatory and cancer related genes in six H3.3K27M DIPG patient-derived primary neurosphere cell lines. We identified gene dependencies in chromatin regulators, polycomb repressive complexes 1 and 2 (PRC1 and PRC2), histone demethylases, acetyltransferases and deacetylators as novel tumor cell dependencies in DIPG. We hypothesized that targeting dysregulated functions of chromatin regulators by genetically deleting and chemically targeting these epigenetically induced vulnerabilities, we could ameliorate, or even reverse the downstream oncogenic effects of the aberrant epigenetic landscape of DIPG. In our secondary CRISPR nanoscreen, we first used six single guide RNAs (sgRNA) to knockout each gene using CRISPR/Cas9 ribonucleoprotein nucleofections, followed by use of three best sgRNAs combined with homology directed repair templates. Compared to lentiviral delivery, nucleofection is a rapid method, with reduced off-target toxicity, suitable for single gene knockouts in DIPG neurospheres. Secondary CRISPR validations confirmed dependencies in BMI1, CBX4, KDM1A, EZH2, EED, SUZ12, HDAC2, and EP300 . Next, we conducted a chemical screen using 20 inhibitors and degraders to target the aberrant activity of HDAC, KDM1A, P300/CBP, PRC1 and PRC2. We identified eight chemical compounds that were effective in H3.3K27M DIPG neurosphere cell lines at low drug concentrations. Among these, an inhibitor and degrader targeting P300/CBP activity indicates a novel strategy of epigenetic therapy in DIPG. Through our combinatorial testing, we will identify a synergistic combination of epigenetic therapy for treating children diagnosed with H3.3K27M DIPG.